THE EFFECTIVENESS OF WORD SEARCH PUZZLE MEDIUM IN VOCABULARY MASTERY - Mulingka Vini; Paula Hampp; Fivy Andries (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study aimed to find out the effectiveness of Word Search Puzzle medium in vocabulary mastery. The research was conducted at SMP Negeri 13 Manado. The research design used quantitative research design through pre-experimental research, which includes a pre-test and a post-test. In the pre-test and post-test, there are 3 instruments, namely multiple choice, short answer, and matching, and the instrument consists of 10 numbers of multiple choice, 10 numbers of short answer, and 10 numbers of matching. The total of the question is 30 numbers. The subject in this study was one group of seventh grade students at SMP Negeri 13 Manado, which consisted of 20 students. The data were collected from the results of the Pre-test and Post-test. In this study showed that the results of the students' Post-test scores were higher than the pretest scores, it was proven in the one students got the highest score that 96 and two students got lowest score that 10, whereas in post-test five students got higher score that 100 and one students got lowest score that 73. The average score of pre-test is 48.75 and the average score of post-test is 90.95. Therefore, through the results of data collection, the writer state the effectiveness of using the Word Search Puzzle medium in helping students learn English, especially in mastering English vocabulary.